Analyzing Social Relations in Startup Ecosystems - Escalfoni, Rafael Elias de Lima; Silva, Monica Ferreira; Oliveira, Jonice (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
A startup ecosystem is a creative environment aiming to promote entrepreneurship and innovation. Startups interact with other entities, building a complex social network. Those connections arise from the interdependence and co-evolution ties between different actors, who share resources to achieve common goals. A smart startup ecosystem demands an understanding of the interests and capabilities of each participant. It could allow identifying convergences and possible partnerships that can help in the new business growth. The Coral platform is a social network analysis based approach to assist in evaluating existing relationships in communities. This paper applies the Coral platform to support incubators’ activities in the local community improvements. Our case study investigated the members’ social and technological aspects in a small entrepreneurial group according to the essential indicators defined by managers: experts, reputation, and professional profile.